Rapa Nui (Easter Island)'s Stone Worlds. Issue 1 (24th October 2013) - Hamilton, Sue
Abstract : This article explores the spatial, architectural and conceptual relationships between landscape places, stone quarrying, and stone moving and building during Rapa Nui's statue-building period. These are central themes of the 'Rapa Nui Landscapes of Construction Project' and are discussed using aspects of the findings of our recent fieldwork. The different scales of expression, from the detail of the domestic sphere to the monumental working of quarries, are considered. It is suggested that the impressiveness of Rapa Nui's stone architecture is its conceptual coherence at the small scale as much as at the large scale.